The Representation of Women in Domestic Violence News: A Corpus Linguistic Analysis - Fadzlin, Nurul; Fiany, Fauzul Asta; Khaliq, Abdul (The Future of Education Journal, 2025)
This study aims to analyze how women are represented in news coverage of domestic violence (DV) on the online media platform Kompas.com, using a corpus linguistics approach. A total of 76 news articles were examined using the AntConc software, focusing on frequency, collocation, and concordance analysis of the word “perempuan” (women). The analysis reveals that although the word “women” appears fairly frequently, its representation tends to be passive and institutional. Dominant collocations such as “Komnas Perempuan” (National Commission on Violence Against Women), “violence against women,” and “women’s empowerment” indicate that women are positioned more as objects of state or institutional actions rather than as active subjects. Concordance analysis further reveals that media narratives more often depict women as victims or statistical entities rather than as agents of change. This study highlights the crucial role of media in either sustaining or challenging patriarchal ideological structures in public discourse on domestic violence. The findings underscore the need for a paradigm shift in news reporting so that women are not merely represented as victims but also as active agents in social struggle.